Ecological Grief and the Dual Process Model of Coping with Bereavement - Pihkala, Panu (Religions (Basel, Switzerland ), 2025)
The Dual Process Model of Coping with Bereavement (DPM, by Stroebe and Schut) is a well-known framework in contemporary grief research and counselling. It depicts how mourners oscillate between various tasks and reactions. There is a need to engage more with the intense feelings of loss (Loss-Oriented tasks), but also with other things in life and other parts of the adjustment process after a loss (Restoration-Oriented tasks). This interdisciplinary article applies the framework to ecological grief and extends it to collective levels. While the DPM has been broadened to family dynamics, many subjects of grief are even more collective and require mourning from whole communities or societies. Religious communities can play an important role in this. This article provides a new application called the DPM-EcoSocial and discusses the various tasks named in it, which are ultimately based on the grief researcher Worden’s work. The particularities of ecological grief are discussed, such as the complications caused by guilt dynamics, climate change denial, attribution differences about climate disasters, and nonfinite losses. Grief and grievance are intimately connected in ecological grief, and (religious) communities have important tasks for remembrance, mourning, and witness. The collective processes can lead to meaning reconstruction, transilience, and adversarial growth.